2022
DOI: 10.3390/rs14112717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Prediction of Landslide Susceptibility in Yichang Section of Yangtze River Basin Based on Integrated Deep Learning Algorithm

Abstract: Landslide susceptibility evaluation (LSE) refers to the probability of landslide occurrence in a region under a specific geological environment and trigger conditions, which is crucial to preventing and controlling landslide risk. The mainstream of the Yangtze River in Yichang City belongs to the largest basin in the Three Gorges Reservoir area and is prone to landslides. Affected by global climate change, seismic activity, and accelerated urbanization, geological disasters such as landslide collapses and debr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…To understand the overall pattern of mass movement distribution and mass movement susceptible areas, we performed summary statistics on the distribution of mass movement in each susceptibility class, distribution of susceptibility classes and the frequency ratio of mass movements in each susceptibility class (Figure 11). In general, models with more historical mass movement points concentrated in predicted high-prone areas are considered to have better performance [98]. From Figure 11, it can be found that for the three types of mass movements, only TBMM's results have more than 80% of the mass movement points concentrated in the areas with high and very high susceptibility (81.6%, 80.4%, and 85.1% for debris flow, rockfall and landslide, respectively), and the least mass movements were classified to low and very low-prone areas (6.9%, 5.8%, and 2.5%, respectively).…”
Section: Spatial Pattern Comparison Of the Susceptibility Mapmentioning
confidence: 99%
“…To understand the overall pattern of mass movement distribution and mass movement susceptible areas, we performed summary statistics on the distribution of mass movement in each susceptibility class, distribution of susceptibility classes and the frequency ratio of mass movements in each susceptibility class (Figure 11). In general, models with more historical mass movement points concentrated in predicted high-prone areas are considered to have better performance [98]. From Figure 11, it can be found that for the three types of mass movements, only TBMM's results have more than 80% of the mass movement points concentrated in the areas with high and very high susceptibility (81.6%, 80.4%, and 85.1% for debris flow, rockfall and landslide, respectively), and the least mass movements were classified to low and very low-prone areas (6.9%, 5.8%, and 2.5%, respectively).…”
Section: Spatial Pattern Comparison Of the Susceptibility Mapmentioning
confidence: 99%
“…Mass movements such as landslides, mudflows, and rockfalls emerge as noteworthy geological hazards, imparting considerable impact on the surrounding environment [1] and anthropogenic, economic and environmental consequences [2]. These phenomena predominantly manifest in orogenic terrains, exemplified by the Bokoya Massif situated to the east of Al-Hoceima city in northern Morocco, constituting our designated study locale.…”
Section: Introductionmentioning
confidence: 99%
“…Oversampling or the superior performance of some algorithms can solve the problem of data imbalance [13,14]. The integrated algorithms can also combat the noise in the data [15,16]. However, they are not easy to implement, especially for non-professional technical personnel.…”
Section: Introductionmentioning
confidence: 99%